Effects of Ovariectomy on Kidney Injury in SDT Fatty Rats - Watanabe, Kana; Saigo, Yasuka; Sasase, Tomohiko; Uno, Kinuko; Miyajima, Katsuhiro; Ohta, Takeshi; Maekawa, Tatsuya (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
Postmenopausal women are at a higher risk of developing diabetes, and estrogen can lower blood glucose levels. The purpose of this study was to investigate the effect of ovariectomy (OVX) on the pathology of diabetic nephropathy. Female SD rats and SDT fatty rat underwent bilateral OVX or sham treatment at 6 weeks of age, and their blood and kidneys were collected at 40 weeks of age for blood biochemical and histopathological analyses. OVX treatment resulted in a decrease in blood estradiol levels at 24 and 40 weeks of age. Histopathological analysis revealed that Sham-treated SDT fatty rats showed glomerular atrophy, adhesions, enlargement, mesangial cell proliferation, regenerated tubules, hyaline casts, Armani-Ebstein lesions, tubular dilatation, interstitial inflammatory cell infiltration, and fibrosis. OVX treatment slightly reduced glomerular atrophy and enlargement, renal tubular dilatation, and interstitial inflammatory cell infiltration, while slightly increased or exacerbated mesangial cell hyperplasia, tubular regeneration, and Armani-Ebstein lesions. The above findings suggest that SDT fatty rats are not a practical model to study postmenopausal diabetic nephropathy.